An anthracene based metal–organic framework showing efficient angle-dependent polarized emission, luminescence thermometry, and photoelectronic response. Issue 5 (19th January 2022) - Zhang, Ji-Rui; Zhang, Hao-Yi; Guo, Jia-Hui; Liu, Zi-Han; Ma, Cheng-Yu; Yang, Xiao-Gang; Lu, Xiao-Yan; Qin, Jian-Hua; Ma, Lu-Fang
Abstract : The packing mode/configuration and photophysical performance relationship of an anthracene based MOF was studied by theoretical calculations and experiments. The MOF shows efficient luminescent polarized emission, luminescence thermometry, and photoelectronic response. Abstract : The development of luminescent metal–organic frameworks (MOFs) has attracted extensive attention due to their applications in photoelectric devices, organic light-emitting diodes (OLEDs), anti-counterfeiting, biological imaging and so on. In this work, a novel anthracene based metal–organic framework, [Cd(DCPA)(DMF)]·(H2 O) (1 ) (H2 DCPA = 9, 10-di( p -carboxyphenyl)anthracene), has been successfully synthesized under solvothermal conditions. The highly ordered arrangement and special spatial conformation of the anthracene chromophore play a significant role in the photophysical properties of 1 . The combination of theoretical calculations and experiments shows that the molecular orbitals have good separation for inhibiting the recombination of electrons and holes. Furthermore, the fluorescence emission of 1 can be instantaneously and reversibly tuned between blue and green at different polarizing angles. Temperature-dependent fluorescence measurements indicate a good linear relationship between the maximum emission intensity/wavelength and the temperature for efficient thermochromism and luminescence thermometry. Photoelectric measurements reveal that 1 shows high performance of photocurrent generation under light illumination. Therefore, our research affords a new perspective to extend the application of luminescent MOFs in the fields of polarized emission, thermometry and photoelectronic response.